Brazilian-Portuguese translation and cross cultural adaptation of the activities-specific balance confidence (ABC) scale - Marques,Amelia P. (2013)
BACKGROUND:The Activities-specific Balance Confidence (ABC) scale was developed to quantify the self-perceived level of confidence in performing specific activities without losing balance or becoming unsteady. The ABC scale has been adopted in clinical practice and in research, although cross-cultural differences may impose difficulties in its use.OBJECTIVE: To translate, cross-culturally adapt and verify the intra- and inter-rater reliability of the Brazilian-Portuguese version of the ABC scale and describe the self-perceived balance confidence of elderly Brazilian people. METHOD:The ABC scale was translated and culturally adapted. To verify the intra- and inter-rater reliability, 40 elderly individuals with ages ranging from 60 to 88 years were interviewed. The scale was administered by two raters on the same day and readministered after seven days by rater 1. To test the reliability, we used the intraclass correlation coefficient (ICC).RESULTS: Six items from the ABC scale were considered culturally, semantically or regionally inappropriate and were modified. The intra-rater reproducibility was excellent (ICC=0.94), and the inter-rater reproducibility was very good (ICC=0.80). The self-perception of balance in specific activities of the elderly was considered very good, with an average of 81.7 and scores ranging from 61.2 to 96.7.CONCLUSION: The ABC scale was translated and culturally adapted for the Brazilian population and presents good intra- and inter-rater reliability. The self-perceived balance confidence in elderly Brazilian people evaluated with the ABC scale is moderate.